2018
DOI: 10.1182/blood-2018-99-112183
|View full text |Cite
|
Sign up to set email alerts
|

Disease and Clinical Characteristics of Patients with Essential Thrombocythemia Enrolled in the MOST Study

Abstract: Introduction: Essential thrombocythemia (ET) is a chronic myeloproliferative neoplasm characterized by clonal platelet production and an increased risk for thrombotic and hemorrhagic events. Limited real-world data exist regarding the clinical characteristics and treatment patterns of ET in the United States; most prior data have been generated outside the United States. The Myelofibrosis and Essential Thrombocythemia Observational STudy (MOST) is an ongoing observational study being conducted to describe cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the Evaluation of Xagrid Efficacy and Long-term Safety (EXELS) study, a large observational analysis of patients with high-risk ET across 13 European countries, HU (54.9%) and anagrelide (40.5%) were the most commonly prescribed monotherapies, and HU plus anagrelide was the most common combination therapy (87.6% of patients required combination cytoreductive treatment) [11]. In the USA, the ongoing Myelofibrosis and Essential Thrombocythemia Observational STudy (MOST) found that 93.3% of patients with high-risk ET were receiving ≥1 ET-directed therapy at the time of enrollment [12]. The most common monotherapies were HU (71.6%) and anagrelide (13.1%).…”
Section: Introductionmentioning
confidence: 99%
“…In the Evaluation of Xagrid Efficacy and Long-term Safety (EXELS) study, a large observational analysis of patients with high-risk ET across 13 European countries, HU (54.9%) and anagrelide (40.5%) were the most commonly prescribed monotherapies, and HU plus anagrelide was the most common combination therapy (87.6% of patients required combination cytoreductive treatment) [11]. In the USA, the ongoing Myelofibrosis and Essential Thrombocythemia Observational STudy (MOST) found that 93.3% of patients with high-risk ET were receiving ≥1 ET-directed therapy at the time of enrollment [12]. The most common monotherapies were HU (71.6%) and anagrelide (13.1%).…”
Section: Introductionmentioning
confidence: 99%